Comparison of Australian and American orthodontic clinical approaches towards root resorption - Lim Elaine; Sameshima Glenn; Petocz Peter; Darendeliler Ali (Sciendo, 2012)
Aims: As part of The Rocky Mountain Travelling Fellowship, a pilot survey was conducted to assess current diagnostic and clinical approaches to the management of orthodontic patients in relation to root resorption.